IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM UPAYA MENINGKATKAN KINERJA GURU AQIDAH AKHLAK - Ekowati; Feriansyah; Yuli Habibatul Imamah (UNISAN JURNAL, 2022)
The purpose of this study was to find out the implementation of madrasa-based management in each centralized function in an effort to improve the quality of learning for Aqidah Akhlak subjects at MTs Muhammadiyah Taman Fajar Purbolinggo. This research was conducted at MTs Muhammadiyah Taman Fajar Purbolinggo. This research is a qualitative descriptive field research or evaluates how to implement madrasa-based management in an effort to improve the quality of learning for Aqidah Akhlak subjects at MTs Muhammadiyah Taman Fajar Purbolinggo. The results of this study are 1) curriculum and teaching program management, education staff management, student management, financial management, facilities and infrastructure management and madrasah relationship management with the community. Basically, the implementation of madrasa-based management in various fields has been going well. 2) Supporting and Inhibiting Factors, among others: The bureaucracy still interferes in the evaluation process at MTs Muhammdiyah Taman Fajar, Purbolinggo District, East Lampung Regency, it is proven that there are still joint semester exams and national exams. Whereas in the KTSP the basic competencies have been carried out by the respective subject teachers, the teacher's lack of creativity in choosing approaches, models, methods and learning strategies, the lack of teachers in making learning equipment, and the number of learning hours that are still lacking when the learning process will be applied. contextual methods (Contextual Teaching Learning)